A Scoping Review of Limited English Proficiency and Immigration in Pediatric Surgery - Liu, Olivia; van Gelderen, Evelien; Giwa, Ganiat; Biswas, Arushi; Nair, Shuait; Garcia, Alejandro V.; Chidiac, Charbel; Rhee, Daniel S. (The Journal of surgical research, 2024)
With increasing globalization and diversity, the intersection of immigration and language barriers can impact patient outcomes. This scope review aims to summarize current evidence on immigration and language barriers on pediatric surgical outcomes. A systematic review was conducted according to the Preferred Reporting Items for Systematic Reviews and Meta-Analysis guidelines. Four databases were searched with Medical Subject Heading terms describing pediatric surgery, immigration, limited English proficiency (LEP), and refugees between 2000-2023. Four independent reviewers screened and analyzed texts for final inclusion. Thirty-three studies were included. Ten studies described disease incidence and severity, finding that LEP, immigrant, and refugee patients were more likely to present with severe disease in appendicitis and traumatic injuries. five studies described pain management, finding patients with LEP received fewer pain assessments, waited longer for analgesia, and had more discrepancies in pain scores. Seventeen studies investigated treatment receipt and delay, finding that immigrants and patients with LEP had longer time to and reduced rates of treatment. Seventeen studies described surgical outcomes, finding that patients with LEP have longer length of stay and more postoperative emergency department visits but fewer follow-up appointments. In kidney transplants, patients with LEP and immigrants had worse outcomes, but these trends are not seen in immigrants from Europe. Overall, immigrants and refugees have higher rates of complications and mortality. Immigrants and patients with LEP and are more likely to present with advanced disease and severe injuries, receive inadequate pain management, experience delays in surgery, and suffer more complications. There is continued need to assess the impact of LEP and immigration on pediatric surgery outcomes. •Immigrants, refugees, and patients with limited English proficiency and are more likely to present with more severe disease and traumatic injuries.•Patients with limited English proficiency receive inadequate pain management, experience longer times to analgesia, and have more discrepancy in pain scores.•Immigrants and patients with limited English proficiency have longer waiting times to surgery and reduced rates of treatment receipt.•Immigrants, refugees, and patients with limited English proficiency have worse surgical outcomes, including complications and mortality.•In kidney transplants, patients with limited English proficiency and immigrants had worse outcomes, but these trends are not seen in immigrants originating from Europe.•Experience delays in surgery and suffer more complications. There is continued need to assess the impact of limited English proficiency and immigration on pediatric surgery outcomes.